Graphene-quantum dot hybrid materials on the road to optoelectronic applications - Pham, Chuyen Van; Madsuha, Alfian F.; Nguyen, Thai Viet; Krueger, Michael (Synthetic metals, 2016)
[Display omitted] •Fabrication of QD-graphene hybrid materials.•Charge transfer in QD-graphene hybrid materials.•Application of QD-graphene hybrid materials in solar cells and photodetectors. With its unique properties, graphene has demonstrated not only high potential for various applications, but is also the subject for studying various fundamental physics. However, due to the lack of a band gap in intrinsic graphene, it is very difficult to separate the charges from photo-excitons and manipulate them for useful purposes within graphene itself. This obstructs its use as active material in photovoltaics (PVs) and photodetectors (PDs). This drawback can be overcome by either chemically or physically combining graphene with semiconductor quantum dots (QDs) to form QD-graphene hybrid materials. These hybrid materials possess designable multifunctional or even completely new properties, which are synergetic combinations of the outstanding properties of graphene with the tunable optoelectronic properties of semiconducting QDs. As a result, various achievements in using QD-graphene hybrid materials as active materials in PV and PD applications have been recently demonstrated. This review will provide comprehensive discussions on recent developments in semiconducting QDs-graphene hybrid materials designed towards PVs and PDs applications. First, the synthesis approaches to QD-graphene hybrid materials will be summarized. In the second part, charge transfer processes occurring within these hybrid materials will be discussed, since it is the basic mechanism behind their applications in PVs and PDs. Finally, recent developments in applications of QD-graphene hybrid materials in PVs and PDs will be addressed.